Doped conductive polymers and single-walled carbon nanotubes as charge storage devices. (15th August 2018) - Al-Haik, Mohammad Y; Kabir, Mohammad M; Ayesh, Ahmad I; Haik, Yousef; Aldajah, Saud H
Abstract: Single-walled carbon nanotubes (SWCNTs), introduced as nano-fillers, were used as charge storage elements. Organic semiconducting polymers were produced by doping organic plasticizers with nonconductive polymers. The nano-fillers were embedded along with organic semiconducting and insulating polymers in constructing metal-insulator-semiconductor (MIS) capacitors classified as organic capacitors. The capacitors were constructed by conventional spin-coating method with metallic electrodes fabricated by means of thermal evaporation. A comparative study was investigated on two device configurations that were built. One with the use of the organic semiconducting polymers and the other with commercially available doped silicon wafer as the semiconductor. Capacitance versus voltage measurements were analyzed on the two configurations to evaluate the storage performance of the devices. The results showed that the device that contained the organic polymeric charge transport layer stored more charge in the SWCNT nano-fillers when compared with the device that contained the silicon wafer. The results also depicted that the embedded SWCNTs were responsible for storing the charge when compared with reference devices that did not contain these nano-fillers.